Validation of SAGE III/ISS Solar Occultation Ozone Products With Correlative Satellite and Ground‐Based Measurements. Issue 11 (7th June 2020) - Wang, H. J. Ray; Damadeo, Robert; Flittner, David; Kramarova, Natalya; Taha, Ghassan; Davis, Sean; Thompson, Anne M.; Strahan, Susan; Wang, Yuhang; Froidevaux, Lucien; Degenstein, Doug; Bourassa, Adam; et al.
Abstract: The Stratospheric Aerosol and Gas Experiment III on the International Space Station (SAGE III/ISS) was launched on 19 February 2017 and began routine operation in June 2017. The first 2 years of SAGE III/ISS (v5.1) solar occultation ozone data were evaluated by using correlative satellite and ground‐based measurements. Among the three (MES, AO3, and MLR) SAGE III/ISS retrieved solar ozone products, AO3 ozone shows the smallest bias and best precision, with mean biases less than 5% for altitudes ~15–55 km in the midlatitudes and ~20–55 km in the tropics. In the lower stratosphere and upper troposphere, AO3 ozone shows high biases that increase with decreasing altitudes and reach ~10% near the tropopause. Preliminary studies indicate that those high biases primarily result from the contributions of the oxygen dimer (O4 ) not being appropriately removed within the ozone channel. The precision of AO3 ozone is estimated to be ~3% for altitudes between 20 and 40 km. It degrades to ~10–15% in the lower mesosphere (~55 km) and ~20–30% near the tropopause. There could be an altitude registration error of ~100 m in the SAGE III/ISS auxiliary temperature and pressure profiles. This, however, does not affect retrieved ozone profiles in native number density on geometric altitude coordinates. In the upper stratosphere and lower mesosphere (~40–55 km), the SAGE III/ISS (and SAGE II) retrieved ozone values show sunrise/sunset differences of ~5–8%, which are almost twice as large as what was observed by other satellites or model predictions. This feature needs further study. Key Points: Among the three SAGE III/ISS solar occultation retrievals, AO3 (v5.1) ozone product shows the smallest bias and the best precision The mean biases of AO3 ozone are less than 5% for ~15–55 km in the midlatitudes and ~20–55 km in the tropics. It increases to ~10% near the tropopause The precision of AO3 ozone is ~3% for altitudes 20–40 km. It degrades to ~10–15% in the lower mesosphere (~55 km) and ~20–30% near the tropopause